Pelatihan dan Pendampingan Pembuatan Makanan Sehat, Penerapan Hygiene, Sanitasi bagi Pengurus Lembaga Kesejahteraan Sosial Anak (LKSA) Widhya Asih Badung - Ni Made Erpia Ordani Astuti; I Gusti Ayu Ika Monika P; Sidhi Turker (Jurnal Nirta : Inovasi Multidisiplin, 2024)
Widhya Asih Badung is a Child Social Welfare Institution (LKSA) which is under the auspices of the Widhya Asih Bali Sejahtera Foundation with the Vision "Breaking the chain of poverty in society through caring for underprivileged children in order to create superior human resources and have a better future". LKSA Widhya Asih has 23 childrens and Its location at Jalan Sang Hyang, Cica, Abianbase, Mengwi, Badung. They come from economically disadvantaged families and various other backgrounds. The education undertaken is Elementary School (1 child), Middle School (6 children), Vocational High School (11 children), High School (1 child) and College (4 children). Aims of the training are being made to increase the funds needed by carrying out simple and creative based economic businesses, including selling food under the brand-name name "PAON LKSA". "PAON LKSA" was founded during the COVID-19 pandemic and is still accepting orders for food and snacks both on a large and small scale using a pre-order system. Ability or skills in producing food, including packaging, are potential that need to be developed to be able to produce quality, attractive, delicious-tasting, healthy food. To improve the skills and competence of the management of the LKSA Widhya Asih Badung, It needed many aspects to optimize potential and develop skills by providing training and assistance in the process of making healthy food (Macaroni Schotel, Risol Mayo, and Nuget) and implementing Hygiene and Sanitation through real actions by providing training and assistance to the administrators of the Widhya Asih Badung Child Welfare Institution (LKSA) in making healthy food (Macaroni Schotel, Risol Mayo, and Nuget) as well as implementing hygiene and sanitation.The output of this activity includes: the administrators of the LKSA Widya Asih Badung. They have understanding, knowledge of the types of food ingredients, cooking equipment, as well as the skills to apply appropriate cooking methods in making healthy food (Macaroni Schotel, Risol Mayo, and Nuget).